Polyimine membrane material, preparation method thereof and application of polyimine membrane material in iodine adsorption

By using Schiff base reaction synthesized polyimine membrane materials at room temperature, the problems of complex preparation and difficult recovery of existing porous materials in capturing iodine are solved, and efficient iodine adsorption and material recyclability are achieved.

CN119875048AActive Publication Date: 2025-04-25LANZHOU UNIV

Patent Information

Application Number
CN202510072270.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

In terms of capturing iodine, existing porous materials have problems such as complex preparation process, harsh conditions, easy to agglomerate and difficult to recycle.

Method used

The polyimine film material is synthesized at room temperature by using Schiff alkali reaction, and a film material with high iodine adsorption ability and recyclability is formed by combining crosslinking agent, dialdehyde monomer and diamine monomer.

Benefits of technology

It achieves efficient iodine adsorption and stability. At the same time, due to the properties of the film material, the problem of easy agglomeration of powder materials is overcome, and it has good cost-effectiveness and user-friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875048A_ABST
    Figure CN119875048A_ABST
Patent Text Reader

Abstract

The invention provides a polyimine membrane material as well as a preparation method and application thereof in iodine adsorption, and relates to the technical field of adsorption materials. The preparation method comprises the following steps: mixing a cross-linking agent, a dialdehyde monomer, a diamine monomer and an aprotic solvent to carry out Schiff base reaction, and removing the solvent from the obtained polyimine solution to form a film, so as to obtain a polyimine film material; the cross-linking agent comprises 2, 6-bis (3 ', 4'-diaminophenyl)-4-phenylpyridine and / or tris (2-aminoethyl) amine. The prepared polyimine membrane material has excellent iodine adsorption capacity and adsorption stability; due to the dynamic imine bond, the broken polyimide film material can be remodeled and recovered under the hot pressing condition, and the characteristic of easiness in recovery is realized; the polyimine membrane material also has excellent mechanical properties. Meanwhile, compared with a powder iodine adsorption material, the membrane-based material overcomes the characteristic of easiness in caking, and shows good cost effectiveness and user friendliness; moreover, the polyimine can be prepared only at room temperature, and the process is simple and convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a polyimine membrane material and a preparation method thereof and application thereof in iodine adsorption. Background Art

[0002] Radioactive iodine ( 129 I and 131 I) are common pollutants associated with nuclear power proliferation. They are highly chemically active and have long half-lives (e.g. 129 The half-life of I is 1.61×10 7 Iodine can be absorbed by the body through inhalation, skin contact or ingestion, and then accumulate in the thyroid gland over time. This gradual accumulation can damage blood vessels and tissues, and eventually lead to cancer after a long latent period. For this reason, people have been working hard to explore efficient methods for capturing radioactive iodine. Among the various methods, solid-state adsorption has been recognized as one of the most promising technologies due to its many advantages, such as simple operation, low maintenance cost, and no need for highly corrosive solutions.

[0003] Among them, porous materials (zeolite, activated carbon, covalent organic framework, metal organic framework, etc.) have been considered the most favorable adsorption materials for capturing iodine. This is because porous materials have a high surface area and can theoretically provide a large number of iodine binding active sites, so they are more effective in capturing iodine and other radioactive pollutants. However, the preparation process of the above porous materials is complicated and the conditions are harsh; and these materials are usually in powder form, with serious agglomeration and difficult to recycle. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a polyimine membrane material and a preparation method thereof and application in iodine adsorption. The preparation method of the present invention is simple and can be completed at room temperature, and the prepared polyimine membrane material has both high iodine adsorption capacity and recyclability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a polyimide membrane material, comprising the following steps:

[0007] A cross-linking agent, a dialdehyde monomer, a diamine monomer and a non-protonic solvent are mixed to perform a Schiff base reaction to obtain a polyimine solution; the cross-linking agent includes 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine and / or tris(2-aminoethyl)amine;

[0008] The polyimine solution is desolventized and formed into a film to obtain the polyimine film material.

[0009] Preferably, the diamine monomer includes one or more of diethylenetriamine, disanisidine and 4,4'-dithiodiphenylamine.

[0010] Preferably, the dialdehyde monomer includes one or more of terephthalaldehyde, 2,6-pyridinedicarboxaldehyde and 4-(4-formylphenoxy)-3-methoxybenzaldehyde.

[0011] Preferably, the molar ratio of -NH2 in the cross-linking agent to -NH2 in the diamine monomer is 1:(0.25-4).

[0012] Preferably, the ratio of the total molar amount of -NH2 in the crosslinking agent and the diamine monomer to the molar amount of the aldehyde group in the dialdehyde monomer is 1:1.

[0013] Preferably, the aprotic solvent includes one or more of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.

[0014] Preferably, the temperature of the Schiff base reaction is room temperature, and the time is 3 to 10 minutes; the Schiff base reaction is carried out under stirring or shaking conditions.

[0015] Preferably, the temperature for the solvent removal and film formation is 120° C., and the temperature is raised from room temperature to the solvent removal and film formation temperature within 30 minutes.

[0016] The present invention provides a polyimide membrane material prepared by the preparation method described in the above technical solution.

[0017] The present invention provides application of the polyimine membrane material described in the above technical solution in iodine adsorption.

[0018] The present invention provides a method for preparing a polyimine membrane material. The present invention uses 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine and / or tri(2-aminoethyl)amine as a crosslinking agent, reacts with a diamine monomer and a dialdehyde monomer in an aprotic solvent via a Schiff base to obtain a polyimine solution; and then forms a film from the polyimine solution to obtain a polyimine membrane material. Compared with the prior art, the present invention has the following beneficial effects:

[0019] The polymer skeleton of the polyimine membrane material prepared by the present invention has a large number of imine bonds, and these imine bonds can very effectively bind iodine atoms through strong interactions equivalent to hydrogen bonds. This characteristic ensures the stability of the polyimine material and its efficient adsorption capacity for iodine; when the cross-linking agent is 2,6-bis(3',4'-diaminophenyl)-4-phenylpyridine, a pyridine unit is also introduced. Due to its polarization effect, pyridine-N and imine-N are both rich in electrons and behave as Lewis bases, so they can capture iodine (iodine is a Lewis acid) through charge transfer, so the introduction of the pyridine unit can improve the iodine adsorption capacity of the polyimine; in addition, the electron-rich aromatic skeleton can also adsorb iodine to a certain extent through electrostatic action; in addition, the polymer skeleton of the polyimine membrane material prepared by the present invention has a large number of heteroatoms, and the introduction of N heteroatoms, oxygen heteroatoms and sulfur heteroatoms can improve the polymer's adsorption capacity for iodine to a certain extent, so the polyimine membrane material prepared by the present invention has excellent iodine adsorption capacity and adsorption stability;

[0020] The polyimine membrane material prepared by the present invention contains dynamic imine bonds, which can help the broken polyimine membrane material to be reshaped and restored under hot pressing conditions, so that the material has the characteristic of being easy to recycle;

[0021] The film-based material prepared by the present invention overcomes the characteristic of easy agglomeration compared with the powdered iodine adsorption material, thereby showing good cost-effectiveness and user-friendliness;

[0022] Moreover, the present invention only needs to react at room temperature to prepare polyimine, the process is simple, and overcomes the disadvantage of relatively complicated preparation of traditional iodine adsorption materials (covalent organic frameworks, metal organic frameworks, porous organic polymers, non-porous adaptive crystals, macrocyclic non-porous amorphous materials);

[0023] Furthermore, when the dialdehyde monomer is 4-(4-formylphenoxy)-3-methoxybenzaldehyde, which is a vanillin derivative, the cost of raw materials can be further reduced and the bio-environmental friendliness of the polymer is improved.

[0024] The results of the embodiment show that the iodine adsorption capacity of the polyimine membrane material prepared by the present invention is 1.6-5.73 g / g, and it exhibits excellent adsorption stability. After five cycles of adsorption, the membrane material still retains 94% of the iodine adsorption capacity; after hot pressing at 100°C and 10 MPa pressure for 45 minutes, the sheared polyimine membrane can be completely restored to its original state, and the surface of the reprocessed film is very smooth and has no cracks, and has the characteristics of recyclability; the tensile strength of the polyimine membrane material is 11.5-83.2 MPa, and the mechanical properties are excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of a process for preparing a polyimide membrane material according to an embodiment of the present invention;

[0026] Figure 2 A reaction route for preparing a polyimine membrane material (taking 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine as a crosslinking agent) according to an embodiment of the present invention;

[0027] Figure 3 It is the Schiff base reaction of 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine, diethylenetriamine and terephthalaldehyde;

[0028] Figure 4 It is a Schiff base reaction of tri(2-aminoethyl)amine, dianisidine and 4-(4-formylphenoxy)-3-methoxybenzaldehyde;

[0029] Figure 5 It is the Schiff base reaction of tri(2-aminoethyl)amine, 4,4'-dithiodiphenylamine and 2,6-pyridinedicarboxaldehyde;

[0030] Figure 6 This is the infrared contrast spectrum of polyimide membrane material (PI-40) and raw materials;

[0031] Figure 7 This is the infrared spectrum of polyimide membrane material (PI-20~PI-40);

[0032] Figure 8 The mechanical properties test results of polyimide membrane materials (PI-20~PI-40);

[0033] Fig. 9 Schematic diagram of hot pressing reshaping of fragmented polyimide membrane material (PI-24);

[0034] Fig.10 Schematic diagram of the iodine adsorption device (a) and the color change of the polyimide membrane material before and after iodine adsorption (b);

[0035] Fig.11 This is a bar graph of iodine adsorption performance of polyimide membrane materials (PI-20 to PI-36);

[0036] Fig.12 The test results of cyclic iodine adsorption performance of polyimine membrane material (PI-36);

[0037] Fig.13 This is a bar graph of the iodine adsorption performance of polyimide membrane materials (XC-0 to XC-100);

[0038] Fig.14 This is a bar chart of the iodine adsorption performance of polyimine membrane materials (SPI-0 to SPI-100). DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing a polyimide membrane material, comprising the following steps:

[0040] A cross-linking agent, a dialdehyde monomer, a diamine monomer and a non-protonic solvent are mixed to perform a Schiff base reaction to obtain a polyimine solution; the cross-linking agent includes 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine and / or tris(2-aminoethyl)amine;

[0041] The polyimine solution is desolventized and formed into a film to obtain the polyimine film material.

[0042] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0043] Figure 1 and Figure 2 The schematic diagram and reaction route diagram of the process for preparing polyimide membrane material according to the embodiment of the present invention are respectively Figure 1-2 Provide detailed explanation.

[0044] The invention mixes a crosslinking agent, a dialdehyde monomer, a diamine monomer and a non-protonic solvent to carry out a Schiff base reaction to obtain a polyimine solution (or a polyimine mixed solution).

[0045] In the present invention, the cross-linking agent includes 2,6-bis(3',4'-diaminophenyl)-4-phenylpyridine (Py-TAB) and / or tris(2-aminoethyl)amine. In the present invention, the structure of the 2,6-bis(3',4'-diaminophenyl)-4-phenylpyridine is as shown in Formula I. The present invention has no special requirements on the source of the 2,6-bis(3',4'-diaminophenyl)-4-phenylpyridine, and it can be prepared by commercial products or by a preparation method well known in the art. In the present invention, the diamine monomer preferably includes one or more of diethylenetriamine, disanisidine and 4,4'-dithiodiphenylamine; the dialdehyde monomer preferably includes one or more of terephthalaldehyde, 2,6-pyridinedicarboxaldehyde and 4-(4-formylphenoxy)-3-methoxybenzaldehyde. The structure of the 4-(4-formylphenoxy)-3-methoxybenzaldehyde is shown in Formula II. The present invention has no special requirements on the source of the 4-(4-formylphenoxy)-3-methoxybenzaldehyde, and it can be prepared using commercially available products or preparation methods well known in the art.

[0046]

[0047] In the present invention, the molar ratio of -NH2 in the crosslinking agent to -NH2 in the diamine monomer is preferably 1:(0.25-4), which may be 1:0.25, 1:0.66, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.1, 1:3.2, 1:3.5 or 1:4; the ratio of the total molar amount of -NH2 in the crosslinking agent and the diamine monomer to the molar amount of the aldehyde group in the dialdehyde monomer is preferably 1:1. The present invention uses 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine and / or tris(2-aminoethyl)amine as a crosslinking agent, which can be prepared by controlling the feed ratio with the diamine monomer and reacting with the dialdehyde monomer to obtain a polyimine having an appropriate crosslinking density and a rigid structure (condensation polymerization), thereby enhancing mechanical properties and iodine adsorption capacity.

[0048] In the present invention, the aprotic solvent preferably includes one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone and N,N-dimethylacetamide. The present invention has no special requirements on the amount of the aprotic solvent, as long as the raw materials can be completely dissolved.

[0049] In the present invention, the method for mixing the cross-linking agent, dialdehyde monomer, diamine monomer and aprotic solvent is preferably: dissolving the cross-linking agent and diamine monomer in an aprotic solvent at room temperature to obtain solution one; dissolving the dialdehyde monomer in an aprotic solvent at room temperature to obtain solution two; and adding solution two to solution one under stirring.

[0050] In the present invention, the temperature of the Schiff base reaction is preferably room temperature, and the time is preferably 3 to 10 minutes, which can be 3, 4, 5, 6, 7, 8, 9 or 10 minutes. The time of the Schiff base reaction is calculated from the completion of the addition of the second solution; the Schiff base reaction is preferably carried out under stirring or shaking conditions.

[0051] In the present invention, taking the diamine monomer as diethylenetriamine, the dialdehyde monomer as terephthalaldehyde, and the crosslinking agent as 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine as an example, the reaction involved in the Schiff base reaction is as follows: Figure 3 As shown; Taking the diamine monomer as dianisidine, the dialdehyde monomer as 4-(4-formylphenoxy)-3-methoxybenzaldehyde, and the crosslinking agent as tris(2-aminoethyl)amine as an example, the reaction involved in the Schiff base reaction is as follows Figure 4 As shown; taking the diamine monomer as 4,4'-dithiodiphenylamine, the dialdehyde monomer as 2,6-pyridinedicarboxaldehyde, and the crosslinking agent as tris(2-aminoethyl)amine as an example, the reaction involved in the Schiff base reaction is as follows Figure 5 As shown (since the polymer is a random copolymer, Figure 3 to Figure 5 Its most representative structural parts are shown).

[0052] The present invention can prepare polyimine only at room temperature (stirring or oscillation may be applied), thus overcoming the disadvantage of relatively complicated preparation of traditional iodine adsorption materials (covalent organic frameworks, metal organic frameworks, porous organic polymers, non-porous adaptive crystals, macrocyclic non-porous amorphous materials).

[0053] After obtaining the polyimine solution, the present invention removes the solvent from the polyimine solution and forms a film to obtain the polyimine film material.

[0054] In the present invention, the temperature of the solvent removal film is preferably 120°C, and it is preferably heated from room temperature to the solvent removal film forming temperature within 30 minutes. In the process of heating from room temperature to the solvent removal film forming temperature, the Schiff base reaction further proceeds, and at the same time, the bubbles introduced into the solution can be eliminated. In the present invention, there is no special requirement for the solvent removal film forming time, as long as the solvent is fully removed. In the embodiment of the present invention, the solvent removal film forming time is 4 hours. In the embodiment of the present invention, the solvent removal film is formed by casting, and the specific operation is: cast the polyimine solution on a clean glass plate, and then heat it from room temperature to 120°C in a muffle furnace within 30 minutes, keep warm for 4 hours, and dry the solvent to obtain a polyimine film material.

[0055] The preparation method provided by the invention has a simple and direct synthesis process and is therefore cost-effective and scalable.

[0056] The present invention provides a polyimine film material prepared by the preparation method described in the above technical solution. In the present invention, the polymer skeleton of the polyimine film material has a large number of imine bonds and heteroatoms. These imine bonds can effectively bind iodine atoms through strong interactions equivalent to hydrogen bonds. This characteristic ensures the stability of the polyimine material and its efficient adsorption capacity for iodine; at the same time, when the cross-linking agent uses 2,6-bis(3',4'-diaminophenyl)-4-phenylpyridine, the polyimine film material has a pyridine unit. Due to its polarization, pyridine-N and imine-N are both rich in electrons and behave as Lewis bases, so they can capture iodine (iodine is a Lewis acid) through charge transfer, so the introduction of pyridine units can improve the iodine adsorption capacity of polyimine; in addition, the polyimine film material has an aromatic skeleton rich in electrons, and can also adsorb iodine to a certain extent through electrostatic action. The polyimine film material provided by the present invention has both high iodine adsorption capacity and recyclability, and has excellent mechanical properties, cost advantages and user-friendliness.

[0057] The present invention provides the application of the polyimine membrane material described in the above technical solution in iodine adsorption. The present invention has no special requirements for the application method, and the application method familiar to those skilled in the art can be used. The polyimine membrane material provided by the present invention has excellent iodine adsorption capacity and adsorption stability, and can achieve efficient adsorption of iodine.

[0058] In order to further illustrate the present invention, the polyimine membrane material provided by the present invention, its preparation method and its application in iodine adsorption are described in detail below with reference to examples, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] At room temperature, 0.2063g of diethylenetriamine (DETA) and 0.0918g of 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine (Py-TAB) were added to a single-mouth bottle with a stirring device and fully dissolved in 8mL DMF to obtain solution 1; 0.3353g of terephthalaldehyde (1,4-phthalaldehyde) was added to a single-mouth bottle with a stirring device and fully dissolved in 4mL DMF to obtain solution 2. Subsequently, solution 2 was added to solution 1 under stirring conditions and stirred for 5 minutes. The resulting polyimine mixed solution was then poured onto a clean glass plate, heated to 120°C for 30 minutes (to complete degassing), and then kept at 120°C for 4 hours to completely evaporate the solvent to obtain a polyimine membrane material.

[0061] Embodiments 2 to 6

[0062] The preparation method is basically the same as that of Example 1, except that the ratio of diethylenetriamine to 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine is different, as shown in Table 1, and the solvent (DMF) used in each example is 12 mL. The polyimine membrane materials prepared in Examples 1 to 6 are recorded as PI-X (X=20, 24, 28, 32, 36, 40, where X represents the molar percentage of -NH2 in the pyridine-containing crosslinking agent, i.e., 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine, to the total -NH2 in the crosslinking agent and diethylenetriamine).

[0063] Table 1 Amounts of reaction materials in Examples 1 to 6

[0064]

[0065]

[0066] The chemical structure characterization and performance test of the polyimide membrane material prepared in the example are as follows:

[0067] (I) Chemical characterization of polyimide membrane materials

[0068] Figure 6 This is the infrared comparison spectrum of polyimide membrane material (PI-40) and raw material.

[0069] Figure 7This is the infrared spectrum of polyimide membrane material (PI-20~PI-40).

[0070] like Figures 6-7 As shown, the polyimide film (PI-X) has a wavelength of 2932 and 2860 cm -1 The methylene stretching vibration peak brought by diethylenetriamine is shown at 1694 cm -1 The characteristic peak of aldehyde group at 1643cm -1 The characteristic peak of imine bond appeared at 3400cm -1 The sharp double peaks nearby turned into a blunt single peak. The results show that PI-X films can be successfully synthesized under extremely mild conditions.

[0071] (II) Mechanical properties of polyimide membrane materials

[0072] Figure 8 The mechanical properties test results of polyimide film materials (PI-20 to PI-40) are as follows:

[0073] PI-20: 39.3MPa, PI-24: 83.2MPa, PI-28: 55.1MPa, PI-32: 35.1MPa, PI-36: 30.8MPa, PI-40: 11.5MPa.

[0074] Generally speaking, the mechanical properties of copolymers can be adjusted by adjusting the ratio of different monomers. Figure 8 As shown in the figure, PI-24 film has the best tensile properties. Although the crosslinking density of PI-28, PI-32, PI-36 and PI-40 increases with the amount of crosslinker, their tensile properties show a downward trend. This is because when the crosslinking density is too large, the directional arrangement of the molecular chains will be seriously affected, and the entangled polymer chains will find it difficult to respond to stress in time, resulting in uneven stress distribution and fracture. At the same time, due to the low crosslinking density of PI-20, its tensile properties (39.3MPa) are lower than those of PI-24 film (83.2MPa). In addition, PI-X film shows a typical brittle fracture curve with an elongation at break of 0.52-2.52%. The change in crosslinker content has little effect on the elongation at break of PI-X film. This may be due to the inherent rigidity of PI-X film, which makes the introduction of a small amount of rigid structure insufficient to have a significant effect on its elongation at break.

[0075] (III) Recyclability test of polyimide membrane materials

[0076] The broken polyimide membrane material (PI-24) is reshaped by hot pressing, such as Fig. 9 As shown in Figure 2, after hot pressing at 100°C and 10 MPa for 45 min, the sheared PI-24 film can be completely restored to its original state. The surface of the reprocessed film is very smooth without cracks.

[0077] (IV) Test of iodine adsorption capacity of polyimide membrane materials

[0078] Since the prepared polyimine film has excellent mechanical properties, iodine adsorption was studied on it in order to broaden its application potential.

[0079] Test method: The prepared polyimine membrane material is subjected to a gas iodine adsorption test. Specifically, about 15 mg (mass is recorded as W1) of the prepared polyimine membrane material and excess iodine are cut into a sealed glass bottle (50 mL), heated at 333 K, and after the membrane adsorption is saturated (mass no longer changes), the mass W2 is weighed and recorded, and then the iodine adsorption amount is calculated using the following formula 1 to determine its iodine adsorption capacity:

[0080] Iodine adsorption amount = (W2-W1) / W1 Formula 1.

[0081] Fig.10 Schematic diagram of the iodine adsorption device (a) and the color change of the polyimide film material before and after iodine adsorption (b). The pyridine unit is introduced to improve the iodine adsorption capacity of the PI-X film. Due to their polarization, both pyridine-N and imine-N are electron-rich and behave as Lewis bases. Therefore, they can capture I2 (a Lewis acid) through charge transfer. Similar to most iodine adsorption materials, as the adsorption proceeds, the color of the PI-X film changes from orange-red to purple-black ( Fig.10 (b)).

[0082] Fig.11 The iodine adsorption performance bar graph of polyimine membrane materials (PI-20 to PI-36). The iodine adsorption capacity of each polyimine membrane material is: PI-20: 1.6 g / g, PI-24: 2.13 g / g, PI-28: 2.87 g / g, PI-32: 3.48 g / g, PI-36: 4.07 g / g. The iodine adsorption capacity of PI-X films (PI-20 to PI-36) ranges from 1.6 to 4.07 g / g and increases with the increase of cross-linking agent content. However, the high iodine adsorption capacity causes the PI-40 film to lose its natural form and adhere to the inner wall of the absorber device. Therefore, the iodine adsorption data of the PI-40 film cannot be collected.

[0083] The polyimine membrane material (PI-36) was subjected to a cyclic iodine adsorption performance test. During the cycle, the iodine-adsorbed PI-36 membrane was ultrasonically treated in DMF to dissociate the adsorbed iodine, and then the iodine adsorption continued. Fig.12The results of the cyclic iodine adsorption performance test of the polyimide membrane material PI-36 are shown in Figure 1. PI-36 exhibits excellent adsorption stability. After five cycles of adsorption, the PI-36 film still retains 94% of the iodine adsorption capacity (3.83 g / g).

[0084] Embodiments 7 to 12

[0085] At room temperature, add tri(2-aminoethyl)amine (TREN) and dianisidine to a single-mouth bottle with a stirring device and fully dissolve them in 8mL DMF to obtain solution 1; add 4-(4-formylphenoxy)-3-methoxybenzaldehyde to a single-mouth bottle with a stirring device and fully dissolve it in 4mL DMF to obtain solution 2. Subsequently, solution 2 is added to solution 1 under stirring conditions and stirred for 5 minutes. Then pour the obtained polyimine mixed solution onto a clean glass plate, heat it to 120°C for 30 minutes (to complete degassing), and then keep it at 120°C for 4 hours to completely evaporate the solvent to obtain a polyimine membrane material. The amounts of tri(2-aminoethyl)amine, dianisidine and 4-(4-formylphenoxy)-3-methoxybenzaldehyde used in Examples 7 to 12 are shown in Table 2, respectively. The polyimine film materials prepared in Examples 7 to 12 are denoted as XC-X (X=0, 20, 40, 60, 80, 100, wherein X represents the molar percentage of -NH2 in the cross-linking agent, i.e., tri(2-aminoethyl)amine, to the total -NH2 in the cross-linking agent and dianisidine).

[0086] Table 2 Amounts of reaction materials in Examples 7 to 12

[0087]

[0088] The iodine adsorption capacity of the polyimine membrane materials prepared in Examples 7 to 12 was tested using the same testing method as described in “(IV) Testing of iodine adsorption capacity of polyimine membrane materials” above. Fig.13 It is a bar chart of the iodine adsorption performance of the polyimine membrane materials (XC-0~XC-100). The iodine adsorption amount of each polyimine membrane material in Examples 7~12 is: XC-0: 0.2g / g, XC-20: 3.72g / g, XC-40: 4.63g / g, XC-60: 5.73g / g, XC-80: 5.25g / g, XC-100: 4.67g / g, among which XC-60 has the best iodine adsorption capacity.

[0089] Examples 13 to 18

[0090] At room temperature, tri(2-aminoethyl)amine (TREN) and 4,4'-dithiodiphenylamine were added to a single-mouth bottle with a stirring device and fully dissolved in 8mL DMF to obtain solution 1; 2,6-pyridinedicarboxaldehyde was added to a single-mouth bottle with a stirring device and fully dissolved in 4mL DMF to obtain solution 2. Subsequently, solution 2 was added to solution 1 under stirring conditions and stirred for 5 minutes. The resulting polyimine mixed solution was then poured onto a clean glass plate, heated to 120°C for 30 minutes (to complete degassing), and then kept at 120°C for 4 hours to completely evaporate the solvent to obtain a polyimine membrane material. The amounts of tri(2-aminoethyl)amine, 4,4'-dithiodiphenylamine and 2,6-pyridinedicarboxaldehyde used in Examples 13 to 18 are shown in Table 3, respectively. The polyimine membrane materials prepared in Examples 13 to 18 are recorded as SPI-X (X=0, 20, 40, 60, 80, 100, wherein X represents the molar percentage of -NH2 in the cross-linking agent, i.e., tri(2-aminoethyl)amine, to the total -NH2 in the cross-linking agent and 4,4'-dithiodiphenylamine).

[0091] Table 3 Amounts of reaction raw materials in Examples 13 to 18

[0092] Example Tris(2-aminoethyl)amine(g) 4,4'-Diphenyldisulfide(g) 2,6-Pyridinedicarboxaldehyde(g) Example 13 (SPI-0) 0 0.1863 0.1013 Example 14 (SPI-20) 0.0146 0.1490 0.1013 Example 15 (SPI-40) 0.0292 0.1118 0.1013 Example 16 (SPI-60) 0.0439 0.0745 0.1013 Example 17 (SPI-80) 0.0585 0.0373 0.1013 Example 18 (SPI-100) 0.0731 0 0.1013

[0093] The iodine adsorption capacity of the polyimine membrane materials prepared in Examples 13 to 18 was tested using the same testing method as described in “(IV) Testing of iodine adsorption capacity of polyimine membrane materials” above. Fig.14 This is a bar chart of the iodine adsorption performance of polyimine membrane materials (SPI-0~SPI-100). The iodine adsorption amounts of the polyimine membrane materials in test examples 13~18 are: SPI-0: 1.55g / g, SPI-20: 3.48g / g, SPI-40: 3.81g / g, SPI-60: 4.21g / g, SPI-80: 4.53g / g, SPI-100: 3.10g / g, among which SPI-80 has the best iodine adsorption capacity.

[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a polyimide membrane material, characterized in that: The following steps are involved: A cross-linking agent, a dialdehyde monomer, a diamine monomer and a non-protonic solvent are mixed to perform a Schiff base reaction to obtain a polyimine solution; the cross-linking agent includes 2,6-bis(3′,4′-diaminophenyl)-4-phenylpyridine and / or tris(2-aminoethyl)amine; The polyimine solution is desolventized and formed into a film to obtain the polyimine film material.

2. The preparation method according to claim 1, characterized in that: The diamine monomer includes one or more of diethylenetriamine, disanisidine and 4,4'-dithiodiphenylamine.

3. The preparation method according to claim 1, characterized in that: The dialdehyde monomer includes one or more of terephthalaldehyde, 2,6-pyridinedicarboxaldehyde and 4-(4-formylphenoxy)-3-methoxybenzaldehyde.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of -NH2 in the crosslinking agent to -NH2 in the diamine monomer is 1:(0.25-4).

5. The preparation method according to claim 4, characterized in that: The ratio of the total molar amount of -NH2 in the crosslinking agent and the diamine monomer to the molar amount of the aldehyde group in the dialdehyde monomer is 1:

1.

6. The preparation method according to claim 1, characterized in that: The aprotic solvent includes one or more of N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylacetamide.

7. The preparation method according to claim 1, characterized in that: The temperature of the Schiff base reaction is room temperature, and the time is 3 to 10 minutes; the Schiff base reaction is carried out under stirring or shaking conditions.

8. The preparation method according to claim 1, characterized in that: The temperature for the solvent removal film formation is 120° C., and the temperature is raised from room temperature to the solvent removal film formation temperature within 30 minutes.

9. The polyimine membrane material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the polyimine membrane material according to claim 9 in iodine adsorption.

Citation Information

Patent Citations

  • Polyimide composite material connected by imide bond covalence and preparation method thereof

    CN105647111A

  • Carbon nanotube-polyimine composite material, and preparation method and application thereof

    CN110256808A

  • In-situ self-reinforced polyimine composite material and preparation method thereof

    CN110483716A

  • Graphene aerogel-polyimine composite membrane material and preparation method thereof

    CN112521716A

Cited By

  • Preparation method of polyimine network-based composite adsorption material and application of polyimine network-based composite adsorption material in rapid purification of nuclear medical iodine-containing waste liquid

    CN121652458A

  • Adsorption material for high-humidity and high-temperature iodine-containing aerosol and preparation method thereof

    CN121732131A